The effect of meteorological parameters on the number of renal colic patients - Atescelik, Metin; Yilmaz, Mustafa; Gurger, Mehtap; Yildiz, Mustafa (Springer, 2015)
In this study, we investigated the effect of meteorological parameters on the number of renal colic patients who admitted to the emergency department regarding patients' gender, patients' age and season. Patients who were admitted to the emergency department with renal colic during a year were studied retrospectively. The number of patients admitted daily was divided into groups according to gender, age and seasons, and correlations between the daily meteorological parameters were examined. In our study, a total of 1890 patients were enrolled and of those 64.9 % (n = 1227) were male. The mean age of the patients was 38 +/- A 14.7/years (18-94). The number of patients admitted daily was 5 +/- A 2.9/patients (1-18). Positive correlation was found between the daily number of patients and daily maximum temperature (p < 0.001, r = 0.212), and daily minimum temperature (p = 0.003, r = 0.160) and daily temperature difference (p < 0.001, r = 0.218). Additionally, a negative correlation with the daily relative humidity (p = 0.001, r = -0.169) was detected. As a result of multivariate regression analysis, age was found to independently affect the number of RC patients admitted to the emergency department (R (2) 0.0079, t -3.56, p < 0.001). Negative correlation was found between relative humidity and female patients, patients in the 30-39 years of age group, and the daily number of RC patients admitted in spring. We found positive correlation between temperature and the number of patients under the age of 39 years, but we concluded that the daily number of patients above the age of 40 years did not significantly correlate with temperature rise. In our study, we determined that meteorological parameters have an effect on renal colic and that this effect varies depending on the patients' age, patients' gender and season.
Keywords: Emergency services; Daily relative humidity; Maximum temperature; Meteorological parameters; Renal colic